Effect of Drying Temperature and Storage Temperature Simplisia on Antioxidant Activity of Herbal Tea Sungkai Leaf (Peronema canescens Jack) - Alfiyah, Dima; Riski Sulistiarini; Supriatno Salam (Journal of Pharmaceuticals and Natural Sciences, 2024)
Sungkai leaves are plants used by the community as an alternative medicine in treating diseases such as malaria, fever, poisoning, and child spasms, as well as postnatal treatment where sungkai leaves are processed into herbal brew. This study aims to determine the best drying and storage temperatures based on the antioxidant activity of sungkai leaf herbal brew. The research method is drying with wind dry temperature, Oven (40oC), and Roast (80oC). Afterward, wind-dry drying was stored for 1 week at room temperature in, an incubator (35oC), and refrigerator (4oC). Then it was made into a brew and tested for antioxidant activity by the DPPH method. The results showed that the best drying temperature antioxidant activity was obtained using oven temperature with an IC50 value of 16.76 ppm. At the same time, the best storage temperature was obtained in incubator storage with IC50 of 36.76 ppm.